No Added Neuroprotective Effect of Remote Ischemic Postconditioning and Therapeutic Hypothermia After Mild Hypoxia-Ischemia in a Piglet Model - Andelius, Ted C. K.; Pedersen, Mette V.; Andersen, Hannah B.; Andersen, Mads; Hjortdal, Vibeke E.; Pedersen, Michael; Ringgaard, Steffen; Hansen, Lærke H.; Henriksen, Tine B.; Kyng, Kasper J. (Frontiers in Pediatrics, 2020)
Introduction: Hypoxic ischemic encephalopathy (HIE) is a major cause of death and disability in children worldwide. Apart from supportive care, the only established treatment for HIE is therapeutic hypothermia (TH). As TH is only partly neuroprotective, there is a need for additional therapies. Intermittent periods of limb ischemia, called remote ischemic postconditioning (RIPC), have been shown to be neuroprotective after HIE in rats and piglets. However, it is unknown whether RIPC adds to the effect of TH. We tested the neuroprotective effect of RIPC with TH compared to TH alone using magnetic resonance imaging and spectroscopy (MRI/MRS) in a piglet HIE model. Methods: Thirty-two male and female piglets were subjected to 45-min global hypoxia-ischemia (HI). Twenty-six animals were randomized to TH or RIPC plus TH; six animals received supportive care only. TH was induced through whole-body cooling. RIPC was induced 1 h after HI by four cycles of 5 min of ischemia and 5 min of reperfusion in both hind limbs. Primary outcome was Lac/NAA ratio at 24 h measured by MRS. Secondary outcomes were NAA/Cr, diffusion-weighted imaging (DWI), arterial spin labeling, aEGG score, and blood oxygen dependent (BOLD) signal measured by MRI/MRS at 6, 12, and 24 h after the hypoxic-ischemic insult. Results: All groups were subjected to a comparable but mild insult. No difference was found between the two intervention groups in Lac/NAA ratio, NAA/Cr ratio, DWI, arterial spin labeling, or BOLD signal. NAA/Cr ratio at 24 h was higher in the two intervention groups compared to supportive care only. There was no difference in aEEG score between the three groups. Conclusion: Treatment with RIPC resulted in no additional neuroprotection when combined with TH. However, insult severity was mild and only evaluated at 24 h after HI with a short MRS echo time. In future studies more subtle neurological effects may be detected with increased MRS echo time and post mortem investigations, such as brain histology. Thus, the possible neuroprotective effect of RIPC needs further evaluation.